Inflammatory response associated with pulmonary complications in non-HIV immunocompromised patients. Issue 12 (24th November 2004) - Agustí, C; Rañó, A; Rovira, M; Filella, X; Benito, N; Moreno, A; Torres, A
Abstract : Background: A study was undertaken to evaluate the local and systemic inflammatory response associated with pulmonary complications in immunocompromised patients and potential implications regarding severity and prognosis. Methods: Levels of different inflammatory mediators were measured in the bronchoalveolar lavage (BAL) fluid and serum on days 1 and 4 after the identification of the pulmonary complication in 127 patients with different immunosuppressive conditions. Results: Pulmonary complications were characterised by a high percentage of neutrophils and increased levels of tumour necrosis factor (TNF)-α, interleukin (IL)-6, IL-8 and IL-10 in the BAL fluid and high serum levels of TNF-α, IL-6, and plasma C-reactive protein (CRP). The inflammatory response was similar in the different groups of immunocompromised patients evaluated. The levels of proinflammatory cytokines were higher in patients with pulmonary infections, particularly those of bacterial aetiology. Patients with a more severe pulmonary infection had a more intense local and systemic inflammatory response. A BAL fluid IL-6 level of >40 pg/ml was an independent predictor of mortality (OR 4.65, 95% CI 1.3 to 16.1), together with a need for mechanical ventilation (OR 13.5, 95% CI 3.2 to 57.3). Patients who died had persistently high levels of CRP on day 4. Conclusions: The evaluation of the inflammatory response, particularly the determination of IL-6 levels in the BAL fluid and CRP in the serum, may be useful for deciding the appropriate management of pulmonary complications in immunocompromised patients.